Power optimization in multi-processor system with frequency scaling and processor affinity - Wee, Adrian Siong Min (Faculty of Computer Science and Information Technology, 2010)
In modern computing system, pocessor technology has evolved tremendously with ever increasing processor frequency and number of processors cores. With better perfomance in processing power, more power is utilized. The objective of this research is to propose a power optimization algorithm in a multi-processors system, by combaining frequency scaling and processor affinity. Lastly, the powe optimization algorithm, using frequency scaling and processor affinity with the optimum configuration, is presented and verified through various test scenarios and test cases.